The Economics of electricity markets theory and policy - Ranci, Pippo; Cervigni, Guido (Loyola de Palacio series on European energy policy., 2013)
The Economics of Electricity Markets provides a cutting-edge analysis of the critical issues involved in the design and operation of electricity markets, as well as an assessment of alternative institutional arrangements that have either been implemented or are under discussion in Europe and the US. The book illustrates how a sound market design can render electricity trading and retailing very much like that of other commodities. Social and political concerns, rather than engineering or economics, are what make electricity markets 'special'. The expert contributors address a wide set of issue.